Submission of proposals for objection and counter-enforcement in the Basic Courts of the Republic of North Macedonia during the period 2016-2019 - Etemi-Ademi, Bukurije (Acta Universitatis Danubius. Juridica, 2022)
During the enforcement process, parties, participants and third parties have the right to file legal remedies in order to protect themselves from the illegalities committed during the enforcement. These illegalities refer to both the enforcement document and the activity of the bailiff. Since the privatization of the enforcement system in RNM, public opinion has expressed dissatisfaction and distrust regarding the transfer of powers to private bailiffs, leaving the courts with the power to decide only on legal remedies. The idea of this research is to analyze how the requests of citizens for objection and counter-enforcement submitted to the Basic Courts of the RNM have continued since 2016 when the new Enforcement Act was brought, until 2019. The data have been processed by statistical methods and are compared with the population number for each judicial district and the data of the Bailiffs Chamber of the RNM on the number of cases enforced for each respective year. In this context, the results show a positive relationship between the cases of counter-enforcement and the population at 35.35%, while this correlation seems to be much stronger between the objections and the population at 90.46%. It was found that citizens generally file objections, but with special emphasis was found an increase in the number of objections in the Basic Court Skopje II for 2018, followed by the Basic Court in Kumanovo for 2017. In terms of requests for counter-enforcement in the Basic Court of Prilep for 2017 also sees a high increase or impulse of demand. In the period 2016-2019, the proposals for objection and counter-enforcement result to coincide with any increase or decrease in the percentage of enforcement by bailiffs. These and other results ascertained make this study important for both theory and practice of enforcement, given the great lack of studies in the field of enforcement and especially regarding the legal remedies available to the citizens of RNM.